VD_FINDINFO Faillite / 2009 / 26 vom 27. August 2009 - VD Tribunal cantonal (2009)
AJOURNEMENT DE LA FAILLITE, PROCÉDURE DE FAILLITE, RÉVOCATION DU SURSIS CONCORDATAIRE | 173a LP, 174 LP, 297 al. 1 LP